2021
DOI: 10.1039/d1sm00038a
|View full text |Cite
|
Sign up to set email alerts
|

Sequential and cellular detection of copper and lactic acid by disaggregation and reaggregation of the fluorescent panchromatic fibres of an acylthiourea based sensor

Abstract: We report for the first time self-assembly of an acyl-thiourea based sensor, N-{(6-methoxy-pyridine-2-yl) carbamothioyl}benzamide (NG1) to panchromatic fluorescent fibres and its dual-sensing properties for the sequential detection of Cu2+ ions...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

6
3

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 75 publications
(23 reference statements)
0
31
0
Order By: Relevance
“…39 In other work, we reported the self-assembly property of acyl thiourea based organic molecule and its applications for the sequential detection of copper and lactic acid. 41 Recently, we also reported lotus-like self-assembled structures formed by a new AIEE dye andits application in sensing and bioimaging. 40 Hence, from our previous studies, we motivated to study the self-assembly of modified single amino acids to assess their applications as functional materials in the future.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…39 In other work, we reported the self-assembly property of acyl thiourea based organic molecule and its applications for the sequential detection of copper and lactic acid. 41 Recently, we also reported lotus-like self-assembled structures formed by a new AIEE dye andits application in sensing and bioimaging. 40 Hence, from our previous studies, we motivated to study the self-assembly of modified single amino acids to assess their applications as functional materials in the future.…”
Section: Introductionmentioning
confidence: 97%
“…Our group are interested to study the self-assembly of single amino acids, 2, 5, 32, 33 modified single amino acids, 4,27 peptides, [34][35][36][37] and heterocyclic compounds. [38][39][40][41][42] Recently, our group has been reported the self-assembly of non-aromatic single amino acids cysteine and methionine formed a amyloid-like fibrillar structures. 2 In another studies our group has also reported the self-assembled structure formation by Proline (Pro), hydroxyproline (Hyp), and lysine.HCl (Lys) to globular, fibrillar, and tape-like self-assembled structure at various ageing time and increasing concentration.…”
Section: Introductionmentioning
confidence: 99%
“…32 In another study mechanical properties of Fmocdiphenylalanine were studied 33 and also the self-assembly of Fmoc-peptides was used for the preparation of nanostructures and hydrogels, 34 Our group has been interested in assessing the self-assembling properties of single amino acids, 3,35 peptides, [36][37][38] and heterocyclic compounds. 10,[38][39][40][41][42] Recently, we reported selfassembled structure formation of cysteine and methionine and its amyloid like characteristic. 3 In other study our group has also reported the self-assembled structure formed by proline, hydroxyproline 35 and lysine.HCl.…”
Section: Introductionmentioning
confidence: 99%
“…Since our group has been working on the molecular self-assembly and assessing the selfassembly of the single amino acids, 8,9,17,18 modified single amino acids, 19 peptides, [20][21][22][23][24][25][26] nanoparticle/nanomaterial, [27][28][29] and heterocyclic [30][31][32][33][34][35] compounds. Our group reported for the very first time the amyloid-like self-assembled structure formed by the non-aromatic single amino acid cysteine and methionine 8 .…”
Section: Introductionmentioning
confidence: 99%